2023
DOI: 10.1088/1361-665x/acceea
|View full text |Cite
|
Sign up to set email alerts
|

Design of a programmable particle filtering medium using a novel auxetic metamaterial

Abstract: This manuscript aims to design and develop a 2D auxetic filtering medium with programmable geometric features specifically designed to vary under in-plane tensile strain. This feature empowers the filtering medium to control the particles separation. A novel design and optimisation algorithm developed in Matlab® determines the final optimized geometry of the filtering medium based on the desired particle size input. Upon thorough numerical investigation, an empirical relationship between the linear elastic in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Given its ability to tackle complex optimisation problems, for instance, where there is a high chance of falling into a local minima during the optimisation process, or when the problem involves optimising multiple conflicting objectives, the GA serves as a strong tool in the pursuit of optimal solutions [35]. The GA has been implemented in several previous studies focused on the design of AM, such as the optimisation of auxetic metamaterials [23] and the material optimisation of biomedical composite devices [36].…”
Section: Parametric Shape Optimisation Of Bcc Structures Through the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given its ability to tackle complex optimisation problems, for instance, where there is a high chance of falling into a local minima during the optimisation process, or when the problem involves optimising multiple conflicting objectives, the GA serves as a strong tool in the pursuit of optimal solutions [35]. The GA has been implemented in several previous studies focused on the design of AM, such as the optimisation of auxetic metamaterials [23] and the material optimisation of biomedical composite devices [36].…”
Section: Parametric Shape Optimisation Of Bcc Structures Through the ...mentioning
confidence: 99%
“…Topology optimisation techniques [20] can be utilised to find the best material distribution, member connectivity, or position of the holes within a lattice unit cell [21]. In contrast, shape optimisation techniques aim to determine the best shape for a structure, while topology, i.e., the connectivity of the strut members within the unit cell, remains unchanged throughout the optimisation process [22,23] as demonstrated in Figure 1b for a BCC structure. Parametric shape optimisation is a subset of shape optimisation that specifically focuses on varying a predefined set of geometric parameters to optimise the design's performance.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrate novel properties not exhibited by most natural and artificial materials. These properties are usually reversal of common senses, such as negative Poisson's ratio [1,2], negative stiffness [3,4], negative swelling behavior [5], and negative refraction [6,7]. Furthermore, some studies demonstrated how to tune or induce the properties of metamaterials after they are manufactured using temperature [8][9][10], magnetic fields [11], air pressure [12], and other methods, thus achieving more diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flexible MAs have gained considerable interest due to their advantages, including flexible design, simple processing, and broadband absorption capability [2,[21][22][23][24]. MA refers to an artificial composite structure or material that embeds specific unit structures into traditional materials, thereby creating extraordinary physical properties that natural materials lack [25][26][27]. The periodic arrangement of these units allows for tunability of polarization, EM wave propagation, and equivalent EM parameters [28][29][30].…”
Section: Introductionmentioning
confidence: 99%